Energy-efficient smart window based on a thermochromic microgel with ultrahigh visible transparency and infrared transmittance modulation. Issue 32 (9th August 2021) - Zhang, Rong; Xiang, Bo; Shen, Yuchun; Xia, Liru; Xu, Lei; Guan, Qingbao; Tang, Shaochun
Abstract : The smart window is highly transparent to allow solar transmittance at low temperatures, while turns opaque automatically to cut off solar energy gain when exposed in sunlight. Abstract : Both high visible transparency and strong solar modulating ability are highly required for energy-saving smart windows, but conventional responsive materials usually have low transparency and a narrow solar transmittance range. Herein, we report a significant advance toward the design and fabrication of responsive smart windows by trapping a novel V0.8 W0.2 O2 @SiO2 -doped poly( N -isopropyl acrylamide) (PNIPAm) thermochromic microgel within two glass panels. The smart window is highly transparent to allow solar transmittance at low temperatures, while it turns opaque automatically to cut off the solar energy gain when exposed to sunlight. With a remarkably low content (1.0 wt‰) of dopant, the V0.8 W0.2 O2 @SiO2 /PNIPAm (VSP) microgels exhibited an ultrahigh luminous transmittance T lum of 92.48% and solar modulation Δ T sol of 77.20%. This superior performance was mainly attributed to the V0.8 W0.2 O2 @SiO2 doping inducing a reduction in the PNIPAm particle size and a change in the internal structure. Also, W-doping decreased the phase-transition temperature ( T c ) of VO2 from 68 °C to ∼30 °C (close to the T c of PNIPAm), contributing to infrared transmittance modulation. In particular, the smart window showed excellent energy saving during daytime outdoor demonstrations, where the practically achievable cooling temperature reached up to 15.1 °C. This new type of thermochromic microgel offering unique advantages of shape-independence and scalability together with soundproof functionality has potential applications in energy-saving buildings and greenhouses.